Female pattern hair loss: A clinical, pathophysiologic, and therapeutic review - G. Fabbrocini; M. Cantelli; A. Masarà; M.C. Annunziata; C. Marasca; S. Cacciapuoti (Wolters Kluwer, 2018)
Female pattern hair loss (FPHL) is the most common form of alopecia in women. Affected women may experience psychological distress and impaired social functioning. Early diagnosis and initiation of treatment are desirable because treatments are more effective to avoid the progression of hair loss than stimulating regrowth. Typically, a diagnosis of FPHL can be confirmed by review of a patient's medical history and a physical examination alone. Testing a scalp biopsy is diagnostic but usually not required. In women with signs of hyperandrogenism, an investigation for ovarian or adrenal disorders should be performed. Treatment for FPHL is obscured by myths. The aim of FPHL treatment could be two-fold: Reverse or stabilize the process of hair follicle miniaturization. Mild-to-moderate FPHL in women can be treated with oral antiandrogen therapies (cyproterone acetate and spironolactone) and/or topical minoxidil with good results in many cases. If used correctly, available medical treatments arrest the progression of the disease and reverse miniaturization in most patients with mild-to-moderate FPHL. Hair systems and surgery may be considered for selected cases of severe FPHL. Keywords: Androgenetic alopecia, female pattern hair loss, finasteride, minoxidil, platelet-rich plasma